2013
DOI: 10.1002/hed.23329
|View full text |Cite
|
Sign up to set email alerts
|

Primary intraocular ancient schwannoma: A case report and review of the literature

Abstract: We describe herein a case of intrascleral schwannoma with ancient changes arising within the globe of the right eye occupying the subretinal space and completely replacing the vitreous body.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 24 publications
0
6
0
1
Order By: Relevance
“…They alone constitute 25-40% of head and neck tumors [2]. Several cases of extracranial ancient schwannoma have been reported in English literature [2][3][4][5]. However an ancient variant involving CPA is particularly rare and our case presentation is one of them.…”
Section: Introductionmentioning
confidence: 70%
“…They alone constitute 25-40% of head and neck tumors [2]. Several cases of extracranial ancient schwannoma have been reported in English literature [2][3][4][5]. However an ancient variant involving CPA is particularly rare and our case presentation is one of them.…”
Section: Introductionmentioning
confidence: 70%
“…1 This tumor is thought to arise from the Schwann cells of the short or long ciliary nerves that traverse through the uveal tract. 1 A literature review on intraocular schwannoma, by You and colleagues, 1,5,6 found 46 cases as of 2013, and further review of the English literature and English-translated literature revealed only two additional welldocumented cases.…”
Section: Discussionmentioning
confidence: 99%
“…Intraocular schwannoma is an extremely rare benign neoplasm that arises from Schwann cells. To date, there has been no report of malignant intraocular schwannoma (5,16,18). A confirmed diagnosis depends on the immunohistochemical analysis of biopsy results, which can distinguish schwannoma from other spindle-cell tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Uveal schwannoma is also termed a 'pseudomelanoma', as it simulates the most common type of primary intraocular tumor, uveal melanoma; this term reflects the difficulty in clinically distinguishing the schwannoma from uveal malignant melanoma (11)(12)(13). In certain previously reported cases, eyeball enucleation was performed due to a diagnosis of malignant melanoma, and only after subsequent histopathological examination of the surgical specimen was a benign tumor revealed (14)(15)(16)(17)(18). In the present study, the cases of 3 patients with intraocular schwannoma who underwent surgical excision locally, retained the eyeball or even achieved an improvement in visual acuity are reviewed.…”
Section: Introductionmentioning
confidence: 99%